KERAGAAN BENIH HORTIKULTURA DI TINGKAT PRODUSEN DAN KONSUMEN (Studi kasus : Bawang merah, Cabai merah, Kubis dan Kentang) - VALERIANA DARWIS; BAMBANG IRAWAN; CHAERUL MUSLIM (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2004)
Seed and seedling is one of main factors in determining the product of horticultural crops. Theuse seed production on horticultural crops, could be produced by government institution orprivate sector. In the last 21 years (1980 – 2001) the government has released 183 improvedvariety of vegetables, including 26 red onion, red chili, cabbage and potato. These number ismuch Owen compared to number of improved variety of crops. For instance 105 newimproved varieties for rice, 50 varieties for corn and 33 varieties for soybean. The role ofprivate sectors on the horticultural seed is much more dominant to the high demandcommodities and cannot be produced by the farmers it can be seen on the production of redchili seed compared to three other commodities. The performance of seed on the levelconsumer, represented by the farmers in the area production central, namely red onion, redchili in the central Java Province, and potato and cabbage in North Sumatera Province. Thefindings of the study are : the farmers are influencing by the group on the selection of seed tobe use, the role of field extension worker is very limited, the seed has been use by the farmersbefore introducing by government, at any planting time the farmers not always use a newseed, even there are some farmers never used improved variety of potato.